2007
DOI: 10.1152/japplphysiol.00622.2006
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia reduces ischemia- and stimulation-induced myocardial interstitial norepinephrine and acetylcholine releases

Abstract: though hypothermia is one of the most powerful modulators that can reduce ischemic injury, the effects of hypothermia on the function of the cardiac autonomic nerves in vivo are not well understood. We examined the effects of hypothermia on the myocardial interstitial norepinephrine (NE) and ACh releases in response to acute myocardial ischemia and to efferent sympathetic or vagal nerve stimulation in anesthetized cats. We induced acute myocardial ischemia by coronary artery occlusion. Compared with normotherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…We next determined the main vasodilator factor(s) (NO vs. EDHFs) that are affected by Ang II infusion. In U46619preconstricted mesenteric arteries from untreated WT mice, L-NAME markedly inhibited ACh-induced dilation, an effect that was more pronounced at lower (probably more physiological) concentrations of ACh (Kawada et al 1985;Shinoe et al 2005) (dilation at 10 À7 mol/L, 11 AE 4% vs. 41 AE 6% in controls, n = 5, P < 0.05; Fig. 4A), confirming previous results that NO is a major vasodilator factor in this isolated vessel preparation (Chataigneau et al 1999;Zhang et al 2009).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…We next determined the main vasodilator factor(s) (NO vs. EDHFs) that are affected by Ang II infusion. In U46619preconstricted mesenteric arteries from untreated WT mice, L-NAME markedly inhibited ACh-induced dilation, an effect that was more pronounced at lower (probably more physiological) concentrations of ACh (Kawada et al 1985;Shinoe et al 2005) (dilation at 10 À7 mol/L, 11 AE 4% vs. 41 AE 6% in controls, n = 5, P < 0.05; Fig. 4A), confirming previous results that NO is a major vasodilator factor in this isolated vessel preparation (Chataigneau et al 1999;Zhang et al 2009).…”
Section: Resultssupporting
confidence: 87%
“…In U46619‐preconstricted mesenteric arteries from untreated WT mice, l ‐NAME markedly inhibited ACh‐induced dilation, an effect that was more pronounced at lower (probably more physiological) concentrations of ACh (Kawada et al. ; Shinoe et al. ) (dilation at 10 −7 mol/L, 11 ± 4% vs. 41 ± 6% in controls, n = 5, P < 0.05; Fig.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…Conflicting observations have been reported from studies in children undergoing cardiac surgical procedures; one study reported increased catecholamine levels when patients were cooled to 26°C (172); however, another study reported no significant changes in catecolamine levels during surface cooling to 28°C, nor during circulatory arrest and cooling until 18°C (173). In addition, some animal studies suggest that hypothermia reduces ischemiainduced catecholamine release from hypoperfused tissues, while catecholamine secretion from noninjured tissues may increase (174). Thus, catecholamine levels may increase during mild-to-moderate hypothermia, but this phenomenon may be linked to a shivering/stress response and to rewarming rather than to hypothermia per se.…”
Section: Side Effects Of Induced Hypothermiamentioning
confidence: 99%